Master Sorai's responsals : an annotated translation of Sorai Sensei Tōmonsho - Ogyū, Sorai, 1666-1728.; Yamashita, Samuel Hideo, 1946- (Honolulu : University of Hawaii Press, 1994)
Master Sorai's Responsals was to eighteenth-century Japan what The Prince was to Renaissance Italy. Like Machiavelli, Ogyu Sorai (1666-1728) was a humanist scholar who served a prince (one of the shogun's chief lieutenants) and drew on his experiences as a house philosopher and on his vast knowledge of history and political affairs in his work. In 1720, when he began to write the letters that comprise this text, the Tokugawa regime was more than a hundred years old and beset with grave administrative and fiscal problems, about which Sorai had much to say. Samuel Yamashita's impressive translation of this work offers modern readers a rare glimpse of the prevailing political discourse of the day and the specific concepts that rulers had at their disposal as they struggled to manage their domains, find talented men for their bureaucracies, create new sources of revenue, and keep their subjects well fed and happy. Sorai himself, of course, is a presence in the text. He is by tunes earnest, frank, impatient, utterly confident, and occasionally condescending. Unlike his Renaissance counterpart, he is something of an optimist: he was convinced that the introduction of archaic Chinese culture and institutions to Japan would solve its myriad problems. Well-versed in Chinese history, philosophy, religion, medicine, and belles lettres, Sorai holds forth on everything from archaic Chinese divination to Sung poetry and prose. He offers advice on how to become a Confucian gentleman, how to learn to read classical Chinese, and which books to read and which to avoid. He even discusses his belief in a sentient, Chinese-style "heaven," a topic not well understood by modern scholars. Long regarded as one of Sorai's best works, Master Sorai's Reponsals bristles with the sharp and clear opinions of the most influential thinker of Tokugawa Japan
Frontmatter -- CONTENTS -- ACKNOWLEDGMENTS -- 1. Ogyū Sorai: His Life, Context, and Interpreters -- 2. Master Sorai's Responsals -- Glossary -- Index -- About the Author.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
English.
Keywords: Ogyū, Sorai; Philosophy, Confucian -- Early works to 1800.; Philosophy -- Early works to 1800.; Philosophie confucéenne -- Ouvrages avant 1800.; Philosophie -- Ouvrages avant 1800.; PHILOSOPHY -- Eastern; Philosophy; Philosophy, Confucian; Neoconfucianisme; Chinese filosofie; Japan; Early works